Design of Dual-Functional Metaoptics for the Spin-Controlled Generation of Orbital Angular Momentum Beams - Vogliardi, Andrea; Romanato, Filippo; Ruffato, Gianluca (Frontiers in Physics, 2022)
The capability of multiple orbital angular momentum (OAM) modes generation with high resolution and diversified functionalities in the visible and near-infrared regime is challenging for flat and integrated optical devices. Additionally, having a static tiny optical device capable of generating multiple structured spots in space reduces the complexity of optical paths that typically use dynamic optical components and/or many standard elements, leading to unprecedented miniaturization and compactness of optical systems. In this regard, we propose dual-functional transmission dielectric metalenses based on a set of Pancharatnam-Berry phase meta-atoms with different cross-sections, for the combined manipulation of the dynamic and geometric phases. In particular, we present and describe the numerical algorithms for the computation of dual-functional metaoptics and we apply those techniques to the design of optical elements which are able to generate and focus different OAM modes at distinct points in space. In the specific, the designed elements enable the independent or simultaneous manipulation of right-handed and left-handed circularly polarized waves, by acting on the helicity of the input beam to enable or disable a specific optical operation. The theoretical proof-of-concept results highlight the capability of the designed metalenses to generate multiple high-resolution focused OAM modes at different points in space by exploiting the polarization of the incident beam as a degree of freedom, thus providing new integrated optics for applications in the fields of high-resolution microscopy, optical manipulation, and optical communications, both in the classical and single-photon regimes.